Perancangan Fitness Center dengan Inovasi Indoor Jogging Track di Surabaya - Ignatius Ivan Wijaya; Stephanus P Honggowidjaja; Priyo Suprobo (Intra, 2018)
Nowadays, there are a lot of fitness center that facilitate people’s need for health. The design and areas of fitness centers are very diverse due to people’s various needs. One of the needs in fitness center is generating indoor jogging track area. Users will be educated about the importance of cardiovascular exercise, that would be maximized if they do it without any machines. Moreover, it is also quite beneficial to reduce the boredom during the exercise even increase the social relationship among users of the facilities in it. The mision of this project is that people are being educated by the importance of jogging exercise. Indoor jogging track become the main focus in the design of this facility so it needs to be maximized to attract and improve user’s satisfaction. However, the other supporting facilities also need to be considered. Other designed facilities include reception area, café area, fitness area, yoga area, aerobics area, RPM area, and locker room.